Odpowiedź :
Odpowiedź:
a) 2(5a-3)-a-4(3a-2)=0
10a-6-a-12+8=0
-3a+2=0
-3a=0-2
-3a=-2 /:-3
A=0,6
b) 2b-(1-b)=11-b
2b-1+b=11-b
3b-1=11-b
3b+b=11+1
4b=12 /:4
B=3
c) 2/5(x-2)=x+4
2/5 x- 4/5= x+4
2x-4=5+20
2x-4=5x+20
2x-5x=20+4
-3x=24
X=(-8)
d) 3y-2(y-1)=-6
3y-2y+2=-6
y+2=-6
y=-6-2
y=-8
e) 3(3-5y2)=90-5(3y2-2y)
9-15y2=90-15y2+10y
9=90+10y
-10y=90-9
-10y=81
Y=-8,1
f) 1/4z+(z-6)=2/3(z-2)
1/4z+z-6=2/3 z-4/3
3z+12z-72+8z-16
15z-72=8z-16
7z=56
Z=8
g) 5(2-3x2)=3(2-5x2)+x
10-15x2=6-15x2+x
10=6+x
-x=6-10
-x=-4
X=4
h) 0,6(1-x)=0,3(8-x)
0,6-0,6x=2,4-0,3x
-0,6x+0,3x=2,4-0,6
-0,3x=1,8
X=-6
Szczegółowe wyjaśnienie: